Anticorrosion treatment process for locally encapsulated magnesium alloy

By increasing the fluoride salt content in the electrolyte during the microarc oxidation process of locally encapsulated products of magnesium alloy, and introducing phosphate or phytic acid, the problem of easy gum burning of the glued part is solved, and a denser and lower roughness microarc oxidation coating is achieved, and the service life of the product is extended.

CN119530927AInactive Publication Date: 2025-02-28SHANGHAI KINDOE NEW MATERIALS TECH CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510088798.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In products where magnesium alloys require partial glue wrapping and then micro-arc oxidation, the glue wrapping plastic is prone to melt or cause glue burning, resulting in product damage.

Method used

By increasing the content of fluoride salt in the alkaline silicate system and introducing phosphate or phytic acid as additives, the electrolyte formulation is adjusted to reduce the intensity of arc discharge and avoid heat accumulation.

Benefits of technology

It effectively reduces the roughness of the microarc oxidation coating, avoids the glue burning phenomenon in the glue-encapsulated part, and improves the corrosion resistance and service life of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to an anti-corrosion treatment process for a locally encapsulated magnesium alloy, and belongs to the technical field of locally encapsulated magnesium alloy surface treatment. According to the method, dirt and an oxide layer on the surface of the magnesium alloy are effectively removed through sand blasting treatment, the surface roughness is improved, a good adhesion foundation is provided for subsequent electrochemical treatment, and the corrosion resistance of the magnesium alloy is remarkably improved through an oxide film formed by components such as silicate in the electrolyte on the surface of the magnesium alloy. According to the invention, the problem of glue burning at a glue coating part is solved by increasing the content of fluoride salt in an alkaline silicate system and introducing a phosphate additive. The concentration of the fluoride salt is larger than 10 g / L, the content of sodium fluoride is increased, the intensity degree of the arc discharge process can be reduced, generated electric arcs are finer, local electric arc energy is lower, generated heat is more dispersed, the heat is more easily taken away by liquid medicine, and then ablation of plastic at the rubber coating position caused by heat accumulation is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment of partially coated magnesium alloys, and relates to an anti-corrosion treatment process of partially coated magnesium alloys. Background Art

[0002] The trend of thinness and lightness of 3C products has been sought after by consumers, while the shells of traditional 3C products are mostly made of plastic. Although they are light in weight, their ability to prevent electromagnetic interference is not as good as that of metal materials. The unique characteristics of magnesium alloys, such as lightness, beauty, electromagnetic shielding performance, good heat dissipation, excellent specific strength and specific stiffness, and good feel, have led to a rapid rise in the application of 3C products. At present, many shells of mobile phones, laptops, cameras, etc. produced by companies such as Huawei, Apple, and Sony use magnesium alloys. AZ91 material has higher strength, impact resistance, dent resistance, and easy processing properties than conventional magnesium alloys and is widely used in the 3C industry. However, AZ91 magnesium alloy still has the characteristics of high chemical activity of magnesium alloys. It is very easy to be corroded when directly exposed to the atmospheric environment. Anti-corrosion treatment is still an important research direction.

[0003] Magnesium alloy surface treatment technology is an effective way to expand its use scenarios and extend its service life. Therefore, reliable surface treatment technology has become the key to breaking the use of magnesium alloys. The common properties of micro-arc oxidation coatings are strong designability, high coating hardness and good wear resistance. In recent years, micro-arc oxidation technology has gradually been applied to the corrosion protection of magnesium alloys. After continuous improvement by researchers, the application of micro-arc oxidation in the corrosion protection of magnesium alloys has become more and more extensive. Magnesium alloy micro-arc oxidation coatings can improve the corrosion resistance and surface hardness of magnesium alloys. In the micro-arc oxidation of magnesium alloys, the coating hardness can reach 500-1000HV.

[0004] Although micro-arc oxidation technology has been widely used to improve the corrosion resistance of magnesium alloys, when some new demands emerge, such as magnesium alloys that need to be partially coated and then micro-arc oxidized, the plastic coating often melts or even burns, resulting in product damage. Therefore, it has become an urgent problem to perform micro-arc oxidation on AZ91 partially coated products without affecting the appearance of the coated part. Summary of the invention

[0005] The object of the present invention is to provide a partial rubber-coated magnesium alloy anti-corrosion treatment process, which has the characteristics of reducing the roughness of the micro-arc oxidation coating and the micro-arc oxidation process not affecting the rubber-coated part.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface is cleaned with deionized water, and hot air drying is performed after cleaning to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface is subjected to sandblasting treatment, and after the sandblasting treatment, the magnesium alloy surface is purged with nitrogen gas at a flow rate of 20 m / s, the purity of the nitrogen gas is 99.99%, and the purging time is 0.5 h; S3: Micro-arc oxidation treatment The magnesium alloy after surface cleaning is placed in an electrolyte, and a micro-arc oxidation treatment is performed with the magnesium alloy as an anode and the stainless steel plate as a cathode; The electrolyte comprises silicate, ablation inhibitor, pH regulator, burn-in inhibitor, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving silicate in deionized water to obtain a solution A with a concentration of 15-25 g / L; S3.2: dissolving the ablation inhibitor in deionized water to obtain a solution B with a concentration of 10-15 g / L; S3.3: dissolving the pH regulator in deionized water to obtain a solution C with a concentration of 2-8 g / L; S3.4: dissolving the burnout inhibitor in deionized water to obtain a solution D with a concentration of 5-15 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The magnesium alloy after micro-arc oxidation treatment is dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it is subjected to UV secondary curing treatment. After curing, the magnesium alloy is cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process is completed after the surface is dried.

[0007] Furthermore, the parameters of hot air drying in S1 are drying temperature of 70-80° C. and drying time of 40-50 min.

[0008] Furthermore, the sandblasting parameters in S2 are: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 minutes.

[0009] Furthermore, the micro-arc oxidation parameters in S3 are controlled by constant current, and the current density is 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, and the time is 23~35min.

[0010] Furthermore, in S3, the coating thickness obtained by micro-arc oxidation is 28-30 μm.

[0011] Furthermore, the ablation inhibitor in S3 is a fluoride salt, which is one or more of sodium fluoride and potassium fluoride.

[0012] Furthermore, the pH regulator in S3 is one or more of sodium hydroxide and potassium hydroxide.

[0013] Furthermore, the gum burning inhibitor in S3 is phosphate or phytic acid.

[0014] Furthermore, the parameters of the UV secondary curing in S4 are ultraviolet wavelength of 355-365 nm and curing time of 5-10 s.

[0015] The present invention firstly removes dirt and oxide layer on the surface of magnesium alloy by sandblasting, increases the surface roughness, provides a good adhesion basis for subsequent electrochemical treatment, and the oxide film formed on the surface of magnesium alloy by silicate and other components in the electrolyte significantly improves the corrosion resistance of magnesium alloy. The magnesium alloy used in the present invention is AZ91 magnesium alloy.

[0016] The electrolyte has a reasonable ratio of silicate, ablation inhibitor, pH regulator and scorching inhibitor and a moderate concentration, which is conducive to forming a uniform and dense oxide film on the surface of the magnesium alloy. The electrolyte preparation process of the present invention is simple and easy to control, ensuring the consistency and stability of each treatment.

[0017] The present invention increases the ablation inhibitor content of fluoride salt in the silicate system, which can reduce the intensity of the arc discharge process, make the generated arc more dense, the local arc energy is lower, and the generated heat is more dispersed, so that the heat is more easily taken away by the potion, thereby avoiding the accumulation of heat and causing the ablation of the plastic at the encapsulation. The phenomenon manifested in the product is that the surface of the micro-arc oxidation coating is denser and the roughness is lower; at the same time, the introduction of phosphate or phytic acid can increase the micro-arc oxidation film forming speed, reduce the porosity of the oxide film, improve its density, enhance the bonding force with the substrate, and change the composition of the oxide film, while reducing the termination voltage of the micro-arc oxidation. The high or low termination voltage reflects the intensity of the micro-plasma chemical reaction on the substrate surface. Increasing the film forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of the arc discharge. By reducing the voltage of the micro-arc oxidation, the intensity of the reaction is reduced. The excess heat generated by the micro-arc oxidation process can be quickly cooled by the potion, avoiding the accumulation of heat on the plastic and causing the phenomenon of burning of the encapsulated part.

[0018] When the concentration of the ablation inhibitor is less than 10 g / L or the concentration of the burn-out inhibitor is less than 5 g / L, the above-mentioned effect cannot be achieved. When the concentration of the ablation inhibitor is greater than 15, the film formation speed will be accelerated too quickly, which will bring unreliable side effects. Therefore, the concentration of the burn-out inhibitor of the present invention is 5~15 g / L. For cost considerations, the concentration of the ablation inhibitor is 10~15 g / L.

[0019] Therefore, the present invention adds fluoride salt and phosphate or phytic acid additives to the silicate system to jointly solve the technical problem of ablation or burning of plastic partially encapsulating magnesium alloy. In the present invention, the phosphate is selected from potassium phosphate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium hexametaphosphate, potassium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or disodium glycerophosphate.

[0020] After the local encapsulation treatment is completed, it is dried in a nitrogen atmosphere at 70°C to prevent the magnesium alloy from reacting with oxygen in the air at high temperature, causing oxidation or corrosion. The UV secondary curing treatment further enhances the adhesion and corrosion resistance of the oxide film and improves the service life of the magnesium alloy.

[0021] Beneficial effects of the present invention: In mobile phones, notebooks and other products, due to the consideration of signals and other factors, the magnesium alloy skeleton or specific positions of the panel need to be partially encapsulated, and then the product needs to be treated with micro-arc oxidation as a whole, and the appearance of the encapsulated area must not be affected. However, AZ91 magnesium alloy reacts violently in the traditional alkaline silicate system. During the arc discharge stage, the sparks generated by the arc are coarse and bright, resulting in high local instantaneous temperature on the surface of the magnesium alloy in the electrolyte. Micro-arc oxidation also relies on the instantaneous high temperature generated during the arc discharge process to melt and cool the oxide to form a micro-arc oxidation coating. In this process, the higher the voltage, the more violent the reaction, the higher the local instantaneous temperature, and the higher the roughness of the generated micro-arc oxidation coating.

[0022] The current problem of magnesium alloy and local encapsulation process burning glue during micro-arc oxidation is mainly due to the alkaline silicate solution system used in common micro-arc oxidation. The arc discharge stage of micro-arc oxidation reacts violently, and the arc spark is coarse and strong. At this time, the local instantaneous temperature is high, and the heat generated on the surface of the magnesium alloy cannot be quickly cooled by the solution, causing the temperature of the plastic at the junction of the magnesium alloy and the plastic to rise. As the reaction continues, the heat gradually accumulates, eventually causing the plastic to burn. In addition, during micro-arc oxidation, the higher the voltage, the more violent the reaction, and the risk of burning at the encapsulation will also increase.

[0023] Therefore, in view of the above reasons, the present invention adopts the method of increasing the fluoride salt content in the alkaline silicate system and introducing a phosphate additive to jointly solve the problem of glue burning at the encapsulation site.

[0024] The concentration of the fluoride salt of the present invention is greater than 10g / L, which increases the sodium fluoride content, can reduce the intensity of the arc discharge process, make the generated arc more dense, the local arc energy is lower, and the generated heat is more dispersed, so that the heat is more easily taken away by the potion, thereby avoiding the accumulation of heat and causing the ablation of the plastic at the encapsulation. The phenomenon manifested in the product is that the surface of the micro-arc oxidation coating is denser and the roughness is lower. The introduction of phosphate or phytic acid can increase the micro-arc oxidation film-forming speed, reduce the porosity of the oxide film, improve its density, enhance the bonding force with the substrate, and change the composition of the oxide film, while reducing the termination voltage of the micro-arc oxidation. The high or low termination voltage reflects the intensity of the micro-plasma chemical reaction on the surface of the substrate; increasing the film-forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of the arc discharge. By reducing the voltage of the micro-arc oxidation, the intensity of the reaction is reduced; the excess heat generated by the micro-arc oxidation process can be quickly cooled by the potion, avoiding the accumulation of heat on the plastic and causing the phenomenon of burning of the encapsulated part. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0026] Figure 1 The change of terminal voltage during micro-arc oxidation in Example 1 of the present invention and Comparative Example 6; Figure 2 The changes in film thickness and time of the micro-arc oxidation coating of Example 4 of the present invention and Comparative Example 6; Figure 3 The roughness comparison of the micro-arc oxidation coating of Example 1 of the present invention and Comparative Example 6; Figure 4 This is the appearance of the encapsulation after micro-arc oxidation in Example 1 of the present invention; Figure 5 This is the appearance of the encapsulation after micro-arc oxidation in Example 2 of the present invention; Figure 6 This is the appearance of the encapsulation after micro-arc oxidation in Example 3 of the present invention; Figure 7 This is the appearance of the encapsulation after micro-arc oxidation in Example 4 of the present invention; Figure 8 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 1 of the present invention; Fig. 9 This is the appearance of the encapsulation after micro-arc oxidation in Comparative Example 2 of the present invention; Fig.10 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 3 of the present invention; Fig.11 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 4 of the present invention; Fig.12This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 5 of the present invention; Fig.13 This is the appearance of the encapsulated area after micro-arc oxidation in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0028] The magnesium alloy of the present invention is provided by Catcher Technology (Suqian) Co., Ltd., and its material grade is AZ91. It is used in notebook computers. The products involved in the present invention have two types, namely, A shell (product number KINDOE A COVER AG, its size is 322mm*220mm in length*width) and C shell (product number KINDOE C COVER WWAN, its size is 322mm*220mm in length*width); wherein the A shell is the part with the display screen, the B shell is the part with the keyboard (not involved), and the C shell is the base part of the notebook computer.

[0029] Example 1 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 30min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte comprises sodium silicate, sodium fluoride, sodium hydroxide, phytic acid, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 20 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 15 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving phytic acid in deionized water to obtain a solution D with a concentration of 10 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 355 nm and a curing time of 10 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0030] Example 2 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 80°C for 40 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 30min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte includes sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 12 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 7 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0031] Example 3 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 35min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte includes sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 11 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D with a concentration of 5 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0032] Example 4 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 40 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 25min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte comprises sodium silicate, potassium fluoride, potassium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve potassium fluoride in deionized water to obtain a solution B with a concentration of 11 g / L; S3.3: Dissolve potassium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 15 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 355 nm and a curing time of 10 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0033] Comparative Example 1 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 23min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte includes sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 12 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 17 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0034] Comparative Example 2 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 35min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte comprises sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 12 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 4 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0035] Comparative Example 3 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 30min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte comprises sodium silicate, sodium fluoride, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 22 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 8 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 12 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy is dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it is subjected to UV secondary curing with parameters of an ultraviolet wavelength of 355 nm and a curing time of 10 seconds. After curing, the magnesium alloy is cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process is completed after the surface is dried.

[0036] Comparative Example 4 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 30min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte comprises sodium silicate, sodium hydroxide, sodium hexametaphosphate, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 20 g / L; S3.2: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.3: dissolving sodium hexametaphosphate in deionized water to obtain a solution D having a concentration of 15 g / L; S3.4: mixing solutions A, C and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0037] Comparative Example 5 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 35min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 28~30μm; The electrolyte includes sodium silicate, sodium fluoride, sodium hydroxide, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 20 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 12 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.4: mixing solutions A, B and C to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0038] Comparative Example 6 A partial encapsulation magnesium alloy anti-corrosion treatment process, the specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface was cleaned with deionized water, and then dried with hot air at 70°C for 50 minutes to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface was sandblasted. The sandblasting parameters were as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min. After the sandblasting, the magnesium alloy surface after sandblasting was purged with nitrogen at a flow rate of 20 m / s. The purity of the nitrogen was 99.99%, and the purging time was 0.5 h. S3: Micro-arc oxidation treatment The magnesium alloy after surface pretreatment was placed in the electrolyte, and the magnesium alloy was used as the anode and the stainless steel plate was used as the cathode for micro-arc oxidation. The micro-arc oxidation parameters were controlled by constant current, and the current density was 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, the time is 30min, and the partially encapsulated magnesium alloy is obtained. The coating thickness obtained by micro-arc oxidation is 23~25μm; The electrolyte includes sodium silicate, sodium fluoride, sodium hydroxide, and the solvent is deionized water; The preparation method of the electrolyte is as follows: S3.1: dissolving sodium silicate in deionized water to obtain a solution A with a concentration of 18 g / L; S3.2: Dissolve sodium fluoride in deionized water to obtain a solution B with a concentration of 6 g / L; S3.3: Dissolve sodium hydroxide in deionized water to obtain a solution C with a concentration of 4 g / L; S3.5: mixing solutions A, B and C to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The partially encapsulated magnesium alloy was dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it was subjected to UV secondary curing with parameters of an ultraviolet wavelength of 365 nm and a curing time of 5 seconds. After curing, the magnesium alloy was cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process was completed after the surface was dried.

[0039] The electrolyte, time, and coating thickness of the micro-arc oxidation process of the embodiments and comparative examples are summarized in the following table. In the following table, "\" indicates that the concentration of the component is 0 g / L or does not contain the substance; "√" indicates that the appearance of the rubber coating is not affected by the micro-arc oxidation, that is, the rubber coating is not ablated; "×" indicates that the rubber coating part is affected by the micro-arc oxidation process, resulting in ablation of the rubber coating part; the criterion for judging is whether the rubber coating part is ablated during the micro-arc oxidation process, affecting the appearance of the rubber coating part, and "×" indicates that there is an impact, and "√" indicates that there is no impact:

[0040] Figure 1 The voltage changes during micro-arc oxidation of Example 1 and Comparative Example 6 are shown. It can be seen from the figure that the voltage of Example 1 is lower than that of Comparative Example 6. Figure 3 From the roughness comparison, it can be seen that the roughness of the micro-arc oxidation coating of Example 1 is smaller than that of the micro-arc oxidation coating of Comparative Example 6. It can be seen that increasing the concentration of sodium fluoride and introducing a burnout inhibitor can reduce the voltage during micro-arc oxidation and reduce the intensity of micro-arc oxidation during arc discharge. At the same time, it reduces the roughness of the micro-arc oxidation coating and avoids the phenomenon of plastic burnout. Figure 2 From the graph of the change in film thickness and time of the micro-arc oxidation coating of Example 4 and Comparative Example 6, it can be seen that the film forming speed of Example 4 is greater than the film forming speed of Comparative Example 6. The increase in film forming speed can reduce the time required for the entire micro-arc oxidation process and reduce the duration of arc discharge.

[0041] Compare the appearance of the encapsulated area after micro-arc oxidation of the embodiment with that of comparative examples 1-6, see Figure 4-13 It can be seen that only when the concentration of sodium fluoride is increased and the ablation inhibitor is introduced at the same time, and the concentration of sodium fluoride is greater than 8g / L, and the concentration of the ablative agent is 5-15g / L, can the rubber-coated part after micro-arc oxidation be prevented from burning.

[0042] Therefore, the present invention increases the sodium fluoride concentration to 10g / L and introduces phosphate or phytic acid into the silicate system, and the phosphate or phytic acid concentration is within the range of 5-15g / L, so that the terminal voltage of the magnesium alloy is reduced by about 20V during micro-arc oxidation, and the roughness of the micro-arc oxidation coating is reduced, and the time of micro-arc oxidation is reduced. From these aspects, the intensity of micro-arc oxidation during arc discharge is reduced, thereby avoiding the phenomenon of plastic burning.

[0043] For some magnesium alloy products having a large number of sharp edges and sharp angles after mechanical processing, the present invention reduces the severity of the micro-arc oxidation reaction and can reduce the risk of sharp edge and sharp angle ablation caused by tip discharge to a certain extent.

[0044] The electrolyte provided by the present invention can be used not only on magnesium alloy products with rubber coating, but also on magnesium alloy products without rubber coating. Reducing voltage and shortening film growth time can save energy consumption of products and increase production efficiency. In addition, the roughness of the micro-arc oxidation coating of the present invention is significantly reduced compared with the traditional silicate system, and is also applicable to some magnesium alloy products that require surface roughness.

[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A partial encapsulation magnesium alloy anti-corrosion treatment process, characterized in that: The specific process of the process is as follows: S1: Magnesium alloy surface cleaning The magnesium alloy surface is cleaned with deionized water, and hot air drying is performed after cleaning to dry the magnesium alloy surface; S2: Surface pretreatment of magnesium alloy The cleaned magnesium alloy surface is subjected to sandblasting treatment, and after the sandblasting treatment, the magnesium alloy surface is purged with nitrogen gas at a flow rate of 20 m / s, the purity of the nitrogen gas is 99.99%, and the purging time is 0.5 h; S3: Micro-arc oxidation treatment The magnesium alloy after surface cleaning is placed in an electrolyte, and a micro-arc oxidation treatment is performed with the magnesium alloy as an anode and the stainless steel plate as a cathode; The electrolyte comprises silicate, ablation inhibitor, pH regulator, burn-in inhibitor, and the solvent is deionized water; Wherein, the ablation inhibitor is a fluoride salt, and the burnout inhibitor is a phosphate or phytic acid; The preparation method of the electrolyte is as follows: S3.1: dissolving silicate in deionized water to obtain a solution A with a concentration of 15-25 g / L; S3.2: dissolving the ablation inhibitor in deionized water to obtain a solution B with a concentration of 10-15 g / L; S3.3: dissolving the pH regulator in deionized water to obtain a solution C with a concentration of 2-8 g / L; S3.4: dissolving the burnout inhibitor in deionized water to obtain a solution D with a concentration of 5-15 g / L; S3.5: mixing solutions A, B, C, and D to obtain the electrolyte, wherein the pH value of the obtained electrolyte is 12 to 13.5; S4: Post-processing The magnesium alloy after micro-arc oxidation treatment is dried in a nitrogen atmosphere at 70°C with a nitrogen purity of 99.99% for 4 hours. After drying, it is subjected to UV secondary curing treatment. After curing, the magnesium alloy is cleaned with deionized water and allowed to stand at room temperature for 12 hours. The process is completed after the surface is dried.

2. A partial encapsulation magnesium alloy anti-corrosion treatment process according to claim 1, characterized in that: The parameters of hot air drying in S1 are drying temperature of 70-80° C. and drying time of 40-50 min.

3. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: The sandblasting parameters in S2 are as follows: using glass beads with a particle size of 200 mesh for sandblasting, a sandblasting distance of 50 mm, a sandblasting angle of 60°, and a sandblasting time of 10 min.

4. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: The micro-arc oxidation parameters in S3 are controlled by constant current, and the current density is 2A / dm 2 , the frequency range is 1500Hz, the duty cycle is 30%, and the time is 23~35min.

5. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: In the S3, the coating thickness is 28-30 μm obtained by micro-arc oxidation.

6. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: The fluoride salt in S3 is one or more of sodium fluoride and potassium fluoride.

7. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: The pH regulator in S3 is one or more of sodium hydroxide and potassium hydroxide.

8. The method for anti-corrosion treatment of partially coated magnesium alloy according to claim 1, characterized in that: The parameters of the UV secondary curing in S4 are an ultraviolet wavelength of 355-365 nm and a curing time of 5-10 seconds.

Citation Information

Patent Citations

  • Surface decoration method of magnesium alloy glue-coating product and forming product thereof

    CN107779930A

  • Surface treatment fluid for surface treatment of magnesium alloy and aluminum alloy composite parts and method

    CN109913923A

  • Electrolyte and method for preparing black membrane on aluminum alloy surface by using same

    CN110004477A

  • Neutral microarc oxidation electrolyte, method and product of electrolyte

    CN110257874A

  • Magnesium alloy micro-arc oxidation ceramic membrane solution and ceramic membrane preparation method

    CN116288596A